Effects of the Chinese herbal formula San-Huang Gu-Ben Zhi-Ke treatment on stable chronic obstructive pulmonary disease: study protocol of a randomized, double-blind, placebo-controlled trial - Yaqi Zu; Demin Li; Xiang Lei; Hongchun Zhang (Trials, 2019)
Abstract Background Due to the large number of patients, high mortality rate as well as high social costs and economic burden, chronic obstructive pulmonary disease (COPD) has become one of the most important health problems around the world, which has attracted people’s attention. Currently, Chinese herbs have been widely used as alternative medicine (CAM) for COPD patients. The Chinese herbal formula San-Huang Gu-Ben Zhi-Ke (SHGBZK) has shown good clinical efficacy in COPD in preclinical studies. Animal experiments have shown that it has mucosal immune barrier function and can maintain airway wall integrity, reduce inflammatory cell infiltration, promote inflammatory damage repair, and relieve narrow airway conditions. Methods/design This study is a randomized, double-blind, placebo-controlled trial. A total of 100 patients with stable COPD diagnosed with deficiency of lung qi and spleen qi will be recruited and randomly assigned to one of two treatment groups: SHGBZK treatment, N = 50; placebo treatment, N = 50. The two groups will receive basic treatment for COPD according to the 2017 GOLD Guidelines for Chronic Obstructive Pulmonary Disease. Patients will stick to the treatment they used to take as much as possible, and will be given present general treatment when acute exacerbation of COPD occurs during the study. Both groups will receive a 24-week intervention and patient status will be assessed at 24 weeks and then 28 weeks after treatment. After the 24-week treatment, patients will be followed up for another 28 weeks. Outcome measures, including the frequency and duration of acute exacerbation, lung function, traditional Chinese medicine symptom score, exercise capacity, and quality of life will be assessed. Discussion It is hypothesized that SHGBZK will have beneficial effects in reducing the frequency and duration of acute exacerbations, improving the exercise capacity function of patients with stable COPD diagnosed with a deficiencies in lung qi and spleen qi. This study may establish a new treatment method for COPD patients, differentiating it from other drugs in clinical use used for similar clinical indications. Trial registration Chinese Clinical Trial Registry, ChiCTR1800016349. Registered on 26 May 2018.